Bullying, su influencia en el autoestima en una adolescente de 14 años - Napa Yepez, Geovanna Alexandra (2020)
For the study the qualitative approach was defined, not subjected to experimentation, and with a correlational and transversal scope, where the components of the personality were considered as indicators, the planned objectives were achieved, through a qualitative methodology, through the theoretical and empirical model , and its different dimensions and techniques and projective instruments, This case study is feasible and viable since it has the context and the population identified, as well as the economic resources to visit the patient, the techniques and psychological instruments for the application and collection and interpretation of results, the objectives set were achieved, through psychotherapeutic treatment, the adolescent was able to integrate it into the environment, is more tolerable to situations and has responded satisfactorily to her performance in classes, to program recreational activities to improve comunicación and fort Encourage dialogue. It is essential and vital that parents know how to understand and reach agreements with their children.